A Comparative Analysis of the Transformation of Corruption Practices in Indonesia and Malaysia - Adithiya Diar,; Tri Imam Munandar,; Saidatul Nadia Abd Aziz, (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
This study analyses the dynamics of corruption in Indonesia and Malaysia as developing countries, focusing on how corrupt practices have transformed from individual crimes into institutionalized systems legitimized socially and politically. socially and politically. The main research questions include: (1) how the forms and patterns of corruption evolve within the institutional context of developing states; and (2) how written law in Indonesia and Malaysia contributes to both the preservation and control of corruption. This research employs a socio-legal approach using a comparative normative-sociological analysis of anti-corruption regulations, law enforcement institutions, and political practices in both countries. The findings reveal that Indonesia and Malaysia face a paradox in their anti-corruption frameworks: strong normative structures yet weak implementation due to the dominance of political interests, bureaucratic patronage, and limited institutional independence. The transformation of corruption occurs through the institutionalization of patronage and socially accepted gratification practices, embedding corruption within the governance system itself. In conclusion, effective anti-corruption efforts in both countries require structural reforms that reinforce the independence of anti-corruption agencies, promote active participation by civil society, and establish an integrity-based private sector. The law must be liberated from political domination so that it functions not merely as a repressive instrument, but as a means of cultivating public ethics and achieving substantive justice.